Management of Asthma during Pregnancy: Optimizing Outcomes and Minimizing Risk - Namazy, Jennifer A.; Schatz, Michael (Seminars in Respiratory and Critical Care Medicine, 2018)
Pregnancy may be complicated by new onset or preexisting asthma. This article reviews diagnosis and management of asthma in the pregnant patient. Special attention is paid to the challenges in diagnosis and management of this condition during pregnancy. Asthma is one of the most common potentially serious medical problems to complicate pregnancy, and asthma may adversely affect both maternal quality of life and perinatal outcomes. Asthma may adversely affect both maternal quality of life and, perinatal outcomes. Pregnant asthmatics have been shown to be at an increased risk of adverse perinatal outcomes. Optimal management of asthma during pregnancy is thus important for both mother and baby. This article provides an update on the available literature regarding the safety of commonly used asthma medications during pregnancy.
Keywords: asthma; pregnancy; medications